Taiwanese species of Cryptoperla (Plecoptera: Peltoperlidae) - Stark, Bill P. (Illiesia, 2007)
The Taiwanese species of Cryptoperla are reviewed and three species are given formal recognition. Records are given for Cryptoperla formosana (Okamoto), a previously recognized species and a new name, C. klapaleki is proposed for C. formosana (Klapálek). The latter species is redescribed from the holotype and from fresh material, and a new species C. uchidai is also proposed. Unassociated females for one species are described under an informal designation.
Keywords: entomologija; Plecoptera; insekti; vrbnice; Tajvan